Periodontal health in a cohort of subjects with type 1 diabetes mellitus - Margaux Roy; Giacomo Gastaldi; Delphine S. Courvoisier; Andrea Mombelli; Catherine Giannopoulou (Wiley, 2019)
Abstract To evaluate periodontal health and oral health behaviors in a cohort of subjects with type 1 diabetes (T1D), 50 persons with T1D (30 males and 20 females; mean age: 35.2 years) were recruited from the Diabetology Unit of the Geneva University Hospitals; 50 nondiabetic persons matched for gender, age, and smoking status comprised the control group. We assessed periodontal health using the gingival index (GI), plaque index, probing depth (PD), bleeding on probing (BOP), and clinical attachment level (CAL) and recorded self‐reported attitudes and behaviors regarding dental care. The two groups were compared using conditional logistic regression. With respect to the mean PD, CAL, and the mean number of sites with PD >4 mm that bled upon probing, there were no significant differences between the groups. However, subjects with diabetes had significantly more plaque and gingival inflammation and presented more sites with BOP compared with control subjects. Further analysis of the subjects in younger (<40 years) and older (>40 years) cohorts revealed a marked difference in GI between younger healthy and controls, which was also present in older patients and controls but much reduced in magnitude and significance. This marked difference in the gingival health of young versus old diabetic patients to matched controls may provide diagnostic advantages and screening and prevention opportunities to exploit. In spite of similar self‐reported oral hygiene habits and frequency of dental visits, patients with T1D presented more plaque and more inflammation than healthy controls, particularly in the younger subjects. Gingivitis in young T1D patients may be an early indicator for more complicated diabetes and periodontitis in the future. Thus, patients with T1D mellitus should be screened for signs of periodontal disease early and should be motivated and instructed in good oral hygiene practices.